The Analysis of Visitor Behavior to Sibetan Tourism Village, Karangasem Bali - Putra, I Kadek Diana; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 10 Number 1 (March 2023), 2023)
Sibetan Tourism Village is a unique destination based on natural tourism attractions in Bali. The beauty of natural scenery and Salak Agrotourism are excellent tourist attractions for visitors. The COVID-19 pandemic had a significant impact on changes in visitor behavior when traveling. The competitiveness of tourist villages and the unknown reasons for visitors to travel to Sibetan Tourism Village becomes an important to carry out a research related to visitors’ behavior analysis. This research aimed to analyze the behavior of visitors who traveled to Sibetan Tourism Village based on six correlation between latent variables. This research method uses a quantitative approach with a sample of 100 respondent taken collected with accidental sampling method. The data analysis techniques included structural equation modeling (SEM) with the SmartPLS 3.3.5 Student Version analysis tool and qualitative descriptive analysis technique. The results of the analysis of visitors’ behavior to Sibetan Tourism Village in this study indicates that (1) visitor motivation has a significant effect on visitor satisfaction; (2) service quality has a significant effect on visitor satisfaction; (3) visitor satisfaction has a significant effect on the image of the destination; (4) the image of the destination has a significant effect on the intention to revisit; (5) visitor motivation has a significant effect on the intention to revisit; and (6) service quality has no significant effect on the intention to revisit.